2001
DOI: 10.1038/sj.leu.2402049
|View full text |Cite
|
Sign up to set email alerts
|

Screening for herpesvirus genomes in common acute lymphoblastic leukemia

Abstract: There is epidemiological evidence that infection may play a role in the etiology of childhood leukemia in particular common B cell precursor acute lymphoblastic leukemia. A panel of 20 leukemic samples (panel 1) was examined for the presence of four lymphotropic herpesviruses using conventional molecular techniques. A second independent panel of 27 leukemic samples (panel 2), along with 28 control peripheral blood samples from children with other forms of cancer, was tested for the presence of the same four vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 41 publications
2
27
0
1
Order By: Relevance
“…45 Finally, if one assumes that to be directly responsible for transformation, at least one copy of HHV per cell (ie a viral load Ն10 4 copies/100 ng DNA) is necessary, only two patients (1 B-CLL, 1 B-ALL, with respectively, 10 3 and 2.2 × 10 3 copies of EBV/100 ng DNA) approached this level. Therefore, our study confirms the conclusion of a previous study limited to childhood ALL 46 that, taken separately, none of the HHVs found in B-ALL and B-CLL is present at levels high enough to be held responsible for B cell transformation. This was the rationale for trying to identify a novel B cell tropic herpesvirus directly responsible for B cell transformation.…”
Section: Discussionsupporting
confidence: 91%
“…45 Finally, if one assumes that to be directly responsible for transformation, at least one copy of HHV per cell (ie a viral load Ն10 4 copies/100 ng DNA) is necessary, only two patients (1 B-CLL, 1 B-ALL, with respectively, 10 3 and 2.2 × 10 3 copies of EBV/100 ng DNA) approached this level. Therefore, our study confirms the conclusion of a previous study limited to childhood ALL 46 that, taken separately, none of the HHVs found in B-ALL and B-CLL is present at levels high enough to be held responsible for B cell transformation. This was the rationale for trying to identify a novel B cell tropic herpesvirus directly responsible for B cell transformation.…”
Section: Discussionsupporting
confidence: 91%
“…Representative difference analysis (RDA) has been used to screen for anonymous, non-human sequences in the genome of common ALL (cALL) samples and no foreign sequences were detected (Mackenzie et al, 2006). In addition, degenerate PCR screens have not implicated a higher frequency of infection in leukaemia cells than in blood cells from children without leukaemia (MacKenzie et al, 2001). These data seem to provide evidence against direct viral transformation.…”
mentioning
confidence: 81%
“…DNA was extracted from whole blood (500 l) from the samples collected in 2004 using QIAamp DNA blood minikits (Qiagen, Crawley, United Kingdom). All samples were assayed using a real-time quantitative TaqMan PCR based on the pol gene of EBV (17). Where sufficient material was available, the sample was assayed in duplicate (83.5% of samples).…”
mentioning
confidence: 99%